2006
DOI: 10.1016/j.jpainsymman.2006.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses' Knowledge, Attitudes, and Self-Efficacy of Children's Pain Management: Evaluation of an Education Program in Taiwan

Abstract: The purpose of this study was to examine the effectiveness of a pediatric pain education program (PPEP) for student nurses. The sample consisted of 181 licensed student nurses who were enrolled in a nursing school in Taiwan. Student nurses attended a 4-hour PPEP that involved case scenario discussion, video, and lecture. Data were collected by an extensive questionnaire that assessed student nurses' knowledge of, attitudes toward, and self-efficacy in pediatric pain assessment and pharmacological and nonpharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 21 publications
4
46
5
2
Order By: Relevance
“…[16] Hence, implementing these roles necessitate that nursing students achieve a comprehensive solid knowledge of pain and its management in the undergraduate nursing program. Also, how to transfer these behaviors learned from pain management education into the clinical setting.…”
Section: Significance Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…[16] Hence, implementing these roles necessitate that nursing students achieve a comprehensive solid knowledge of pain and its management in the undergraduate nursing program. Also, how to transfer these behaviors learned from pain management education into the clinical setting.…”
Section: Significance Of Studymentioning
confidence: 99%
“…The survey includes 25 true or false questions, 13 multiple choice questions, and two-part case study questions. The PNKAS was selected for use in the study after thorough review of literature on knowledge and attitudes toward pain and pain management in the pediatric population by many researchers as: Chin Tracy (2006), [7] Chiang et al (2006), [16] Ortiz et al (2015) [19] and Laprise (2016). [20] Also, Duke et al (2013), [13] Al-Khawaldeh et al (2013) [9] and Al Omari (2016) [8] who have found it a suitable tool for use with undergraduate nursing students because it was reliable.…”
Section: Tools Of Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,24] A few studies have tested the level of pain assessment and management knowledge among nursing students, and they found that nursing students lack appropriate knowledge. [23,[25][26][27] Previous research alluded to the importance of nurses to have appropriate knowledge regarding pain during their study and integrating pain management topic as a part of nursing syllabus. [21,24] However, in Jordan, lecturers devote only a small proportion of the child health nursing curriculum (theory) to pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings suggest children's nurses (qualified nurses and students) have a poor theoretical understanding of pain. For example Vincent (2005), Chiang et al (2006), and Twycross and Roderique (2011) have identified that the pathophysiology of pain, psychosocial aspects of pain, pain assessment and the pharmacology of analgesics as areas for development. It has been suggested that improvements in children's nurses' knowledge of pain and pain management through educational input does not necessarily inform and influence practice (Vincent andDenyes 2004, Twycross 2007).…”
Section: Introductionmentioning
confidence: 99%